Faktor-Faktor Yang Mempengaruhi Kualitas Laporan Keuangan - Bagas Prinanda; Dea Safira; Dea Wulan Saputri; Eka Khoiriah; Ersi Sisdianto (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This study aims to provide a broader research picture on the topic of financial statement quality. In this study, factors that affect financial statements will be described. The research method used is in the form of literature studies from several national journals with a range of 2020-2023. The results of the study found that factors that can affect the quality of a company's financial statements are internal control systems, human resource competencies, information technology, organizational commitment, data reconciliation, and leadership ethics.